Fibrillisation of faba bean protein isolate by thermosonication for process efficacy: Microstructural characteristics, assembly behaviour, and physicochemical properties - Hu Y; Cheng L; Gilbert EP; Loo TS; Lee SJ; Harrison J; Yang Z (Elsevier Ltd, 2024)
The effect of thermosonication (TS) (90 °C, 10–30 min) on the fibrillisation of faba bean protein isolate (FPI) was studied. The self-assembly behaviour, microstructural characteristics and techno-functional (gelation and emulsification) properties of FPI fibrils obtained from TS treatment were compared with those obtained from conventional prolonged heating (CH) at 90 °C up to 8 h. Compared to CH treatment, TS treatment was shown to significantly accelerate the formation of FPI fibrils with prominent β-sheet structures as revealed by Thioflavin T (ThT) fluorescence, Fourier-transform infrared spectroscopy (FTIR) and circular dichroism (CD). The characteristics of fibril building blocks were analysed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and liquid chromatography linked to tandem mass spectrometry (LC-MS/MS) to obtain the differences between TS and CH induced fibrillisation of FPI. Transmission electron microscopy (TEM) and small-angle neutron scattering (SANS) showed that 4 h CH and 10 min TS treatments resulted in the fibrils with similar radius (from 5 to 10 nm). Furthermore, SANS indicated that TS treatment induced the formation of an entangled FPI fibrillar network, which could lead to the observed viscoelastic properties of FPI at a high concentration (10 wt%). Finally, high internal phase O/W emulsions (HIPE, φ = 0.75) stabilised by 30 min TS induced FPI fibrils (3 wt%) demonstrated a stronger gel strength and smaller oil droplet size compared to those prepared with untreated FPI, suggesting a superior emulsification capability of FPI fibrils. This finding demonstrates that TS treatment is a promising and efficient method for fibrillisation of plant proteins with the resultant fibrils generating excellent gelation and emulsification properties.
Keywords: Thermosonication; Self-assembly fibrils; Faba bean protein isolates; Small angle neutron scattering; High internal phase emulsions; Microstructures